Enhancement of on-time delivery of orders by lean service and planning tools in a commercial company in the mining sector. - Guzman Carrillo, Luis Alexander (2025)
The importance of service level in companies is increasingly vital, whether post or pre- sales, the level should always aim to satisfy the customer. To maintain a good level of service it is necessary that, in each sector, logistics and transportation are reviewed to meet the delivery time agreed with the customer, this avoids a decrease in the customer base and even sales cancellations that affect the final profit. Therefore, it is essential to plan the supply and distribution processes and then review the operation times to seek a standardized process. The proposed proposal uses a Master Plan Schedule (MPS) and Distribution Requirement Planning (DRP) tools to improve supply and distribution management. In another way, the use of Poka Yoke and Work Standardization is also proposed to avoid errors to reduce operating times and seek their standardization. After the implementation of the pilot tests, the increase in the rate of orders delivered on time was achieved by 27%, and the results were supported with a software simulation where the same results were obtained.